2022
DOI: 10.1021/acssuschemeng.1c08737
|View full text |Cite
|
Sign up to set email alerts
|

Selective Reduction of Au(I) from a High-Concentration Thiosulfate Solution for Gold Recovery Using One-Step Heat-Treated High-Sulfur Coal

Abstract: It is challenging to economically, efficiently, and selectively recover Au(S 2 O 3 ) 2 3− from thiosulfate gold leaching solutions. This article reports an approach to effectively recover Au(S 2 O 3 ) 2 3− using a toxic material, high-sulfur coal (HSC). Calcined HSC (CHSC) obtained through the onestep calcination of HSC in an inert environment can effectively adsorb Au(S 2 O 3 ) 2 3− present in a high-concentration thiosulfate solution. While the adsorption process is dominated by chemical adsorption, the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The effective adsorption of gold on Fe 3 O 4 @CuS can be attributed to two primary factors: the strong affinity between sulfur and gold and the redox reaction between Au­(III) and CuS. Numerous studies have demonstrated that adsorbents with high sulfur content exhibit a strong affinity for gold complexes, , which enhances their selective recovery from aqueous solutions. Furthermore, high-resolution XPS analysis of Cu 2p reveals that a portion of Cu + undergo oxidation during gold adsorption.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effective adsorption of gold on Fe 3 O 4 @CuS can be attributed to two primary factors: the strong affinity between sulfur and gold and the redox reaction between Au­(III) and CuS. Numerous studies have demonstrated that adsorbents with high sulfur content exhibit a strong affinity for gold complexes, , which enhances their selective recovery from aqueous solutions. Furthermore, high-resolution XPS analysis of Cu 2p reveals that a portion of Cu + undergo oxidation during gold adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, adsorbents with high sulfur content have been proven to be very effective for capturing and recovering gold complexes. , Gold complexes are attracted to adsorbents with high sulfur content because they form strong chemical bonds with the sulfur atoms in the adsorbent. Thiol or mercaptan functional groups (−SH) on the adsorbents can form strong coordination bonds with gold complexes, allowing the gold to be effectively captured and retained by the adsorbent, and the attraction between sulfur-containing adsorbents and gold complexes is usually highly selective. ,,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the Fermi level of Fe 8 S 9 was higher than that of FeS 2 , the reducibility of CHSC was higher than that of high-sulfur coal, and Au(S 2 O 3 ) 2 3− in solution can be reduced to elemental Au. 23 High-sulfur coal cannot be burned directly, and long-term stacking releases harmful gases, such as SO 2 , H 2 S, and NO 2 , 24,25 and pollutes the surrounding water and soil. Therefore, using high-sulfur coal as an adsorbent for Au(S 2 O 3 ) 2 3− broadens the utilization value of high-sulfur coal and provides a new method for recovering Au(S 2 O 3 ) 2 3− from thiosulfate solutions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The phases of high-sulfur coal before and after calcination were characterized using X-ray diffraction, and it was determined that the primary phase changed from FeS 2 for high-sulfur coal to Fe 8 S 9 for CHSC. Because the Fermi level of Fe 8 S 9 was higher than that of FeS 2 , the reducibility of CHSC was higher than that of high-sulfur coal, and Au­(S 2 O 3 ) 2 3– in solution can be reduced to elemental Au …”
Section: Introductionmentioning
confidence: 99%